Strategi Manajemen Budaya Akademik dalam Meningkatkan Absensi Mahasiswa di STITNU Al-Farabi Pangandaran - Ina Nurwahidah; Hoerudin Hoerudin; Denisa Nurfitriani; Samsudin Samsudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research explores academic cultural practices in the campus environment and its impact on increasing student absenteeism at STIT NU Al-farabi Pangandaran. The method used is participatory descriptive qualitative with a phenomological approach. Data was obtained through complete participant observation and in-depth interviews with students and lecturers as well as analysis of related documents. .The results of the research show that many students at SIT NU Al-Farabi Pangandaran work part time, student involvement in campus organizations and personal problems are the main problems that influence the increase in absenteeism on campus, students who work part time often experience conflicts between schedules. work and study schedules. These findings underscore the need for appropriate intervention by improving academic culture so as to increase lecture attendance on campus, with a focus on flexible time management and improving academic discipline.